2017
DOI: 10.1021/acsnano.6b06979
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cell Capture on Functionalized Graphene Oxide Nanosheets through Oxygen Clustering

Abstract: With the global rise in incidence of cancer and infectious diseases, there is a need for the development of techniques to diagnose, treat, and monitor these conditions. The ability to efficiently capture and isolate cells and other biomolecules from peripheral whole blood for downstream analyses is a necessary requirement. Graphene oxide (GO) is an attractive template nanomaterial for such biosensing applications. Favorable properties include its two-dimensional architecture and wide range of functionalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…Graphene oxide (GO), an atom‐thick sheet of carbon functionalized with rich and interactive oxygen‐containing groups, is unsuitable for application in supercapacitors due to its poor conductivity . The theoretical calculations demonstrate that oxygen functional groups in GO can distribute on the carbon network in the form of clustered structure under certain conditions, indicating the existence of sp 3 carbon with oxygen groups distributed in graphitic domains (sp 2 carbon). It is worth mentioning that the as‐synthesized RGO with different oxygen concentrations of 5–30 at% depends on the reduction of GO under mild or harsh conditions, but the increased electrical conductivity of RGO comes at the expense of the decreased oxygen content .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO), an atom‐thick sheet of carbon functionalized with rich and interactive oxygen‐containing groups, is unsuitable for application in supercapacitors due to its poor conductivity . The theoretical calculations demonstrate that oxygen functional groups in GO can distribute on the carbon network in the form of clustered structure under certain conditions, indicating the existence of sp 3 carbon with oxygen groups distributed in graphitic domains (sp 2 carbon). It is worth mentioning that the as‐synthesized RGO with different oxygen concentrations of 5–30 at% depends on the reduction of GO under mild or harsh conditions, but the increased electrical conductivity of RGO comes at the expense of the decreased oxygen content .…”
Section: Introductionmentioning
confidence: 99%
“…This linkage was found to have a high degree of mechanical stability and also demonstrates that click reactions can occur without interfering with natural biochemical processes that occur in organisms in vivo, which is tremendously beneficial for future diagnostic applications. Previously, a research group had used GO as a substrate in combination with single-domain antibody, protein modification, and click chemistry technologies so that the antibody can be immobilized unidirectional on the GO substrate, thereby establishing a functional device that can rapidly capture a small number of specific cells from the blood [100]. Other related studies have demonstrated that when antibodies are immobilized to a substrate by click chemistry, target specificity and sensitivity are greatly enhanced in addition to effectively maintaining the activity of the biological probe [101,102] (Figure 7A-D).…”
Section: Application Of Nanomaterials In Microfluidic-based Systems Fmentioning
confidence: 99%
“…In addition, several nanomaterials such as carbon nanotubes [15], graphene-oxide nanosheets [16], nanowires and magnetic nanoparticles [17][18][19][20][21] have been investigated for the capture of CTCs.…”
Section: Introductionmentioning
confidence: 99%